Age and reasons for first dental visit and knowledge and attitude of parents toward dental procedures for Puducherry children aged 0-9 years - Adimoulame Sanguida; Venkatachalamoorthi Vinothini; Gajula Shivashankarappa Prathima; Arumugam Santhadevy; Kulandairaj Premlal; Muthukrishnan Kavitha (Wolters Kluwer Medknow Publications, 2019)
Background: The first dental visit provides the dentist an opportunity to advise parents on prevention of oral diseases and also allows for early detection of caries and arrest of its progression. The first dental visit should occur no later than 12 months of age. However, parents fail to give importance to primary dentition as they feel that they are temporary. Aim: The aim of this study was to determine the age of first dental visit and most common reasons for the visit among children aged 0-9 years and to examine the knowledge and attitude of their parents toward treatment procedures for children, taking into account their socioeconomic and educational status. Materials and Methods: After obtaining informed consent from parents, sociodemographic data that included age and gender of the child, educational status, occupation of parents, and annual family income were collected. A validated questionnaire was given to the parents. Statistical Analysis Used: Descriptive statistics (proportion) was used to report the data. To examine differences in knowledge and attitudes among different socioeconomic and educational groups, chi-square test was used with P value <0.05. Results: A total of 300 completed questionnaires were analyzed. Age of first dental visit was 6-9 years (57%) and the most common reason for the visit was decayed teeth (33%). The overall attitude of parents toward treatment procedures for children was good in spite of low levels of knowledge about primary teeth and role of the pedodontist. Conclusions: It is necessary to promote early dental visits by providing education on perinatal and infant oral healthcare to the healthcare professionals dealing with children. It is also important to promote awareness regarding the maintenance of primary dentition.